Nasal reconstruction using ribs in a patient with Binder syndrome: A case report and literature review - Oona Tomiê Daronch; Renata Fernanda Ramos Marcante; Laisa Brandão Carvalho; Aristides Augusto Palhares (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: Binder’s syndrome can also be known as maxillonasal dysplasia and it is a congenital malformation characterized by nasomaxillary hypoplasia resulting from an underdevelopment of the middle facial skeleton. The current incidence or prevalence is still unknown, but it affects approximately one child in every 10,000 births. The diagnosis can be clinical or associated with prenatal ultrasonography, characterized by a flattened nose and abnormal maxillary convexity. The treatment is surgical to correct aesthetic and functional abnormalities. Case Report: Patient diagnosed with Binder’s syndrome at the age of 14, without other associated malformations, with aesthetic and functional nasal complaints. Surgical correction began with the extraction of a block of the sixth costal cartilage on the left, with a nasal opening on the columellar margin, in the pattern of an open rhinoplasty, and tissue dissection in the sub-SMAS plane. After preparing the nasal receptor area, a block of cartilage was sculpted for reconstruction of the nasal dorsum, alar grafts and septal cartilage grafts. There was an improvement in the projection of the nasal tip and nasal dorsum. Conclusion: Rhinoplasty can be a challenging surgery in these patients, and the literature indicates that the best option is autologous reconstruction with costal cartilage. It is necessary to individualize each case to schedule nasal grafts and restructuring, and functional improvement in these cases is also essential.